2000
DOI: 10.1007/s004030050484
|View full text |Cite
|
Sign up to set email alerts
|

Generation of reactive oxygen species by Candida albicans in relation to morphogenesis

Abstract: Candida albicans is able to generate significant amounts of reactive oxygen species (ROS). In this study, ROS generation by yeast and hyphal forms of the strain 3153 A was analyzed to determine whether ROS generation could be a major factor in the invasive behavior of germinative cells. Furthermore, the virulent strain CA6 and its avirulent and agerminative mutant VIR3 were compared. ROS were measured by lucigenin-enhanced chemiluminescence and a cytochrome c assay. During the blastoconidial phase of all strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
55
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 22 publications
5
55
0
1
Order By: Relevance
“…Given the importance of morphological-phase transitions in fungal virulence (52) and the exposure of fungi to oxidant stress even in the early stages of mammalian host infection, it is tempting to speculate that the morphogenetic mechanisms demonstrated in N. crassa and A. nidulans may extend to fungal pathogens. In fact, evidence of ROS production by C. albicans in relation to morphogenesis has been presented, although a causal relationship has not been demonstrated (156).…”
Section: Role Of Oxidant Stress In Stimulation Of Fungal Cell Differementioning
confidence: 99%
“…Given the importance of morphological-phase transitions in fungal virulence (52) and the exposure of fungi to oxidant stress even in the early stages of mammalian host infection, it is tempting to speculate that the morphogenetic mechanisms demonstrated in N. crassa and A. nidulans may extend to fungal pathogens. In fact, evidence of ROS production by C. albicans in relation to morphogenesis has been presented, although a causal relationship has not been demonstrated (156).…”
Section: Role Of Oxidant Stress In Stimulation Of Fungal Cell Differementioning
confidence: 99%
“…In addition, Schroter et al (2000) analysed the amount of ROS produced when cells were incubated in 10% serum. Those authors found that ROS were produced in large amounts in a strain that formed true hyphae.…”
mentioning
confidence: 99%
“…Consistent with this, Michán and Pueyo 33 reported that the GSH levels in C. albicans hyphae were approximately 50% of those in yeasts. Considering that oxidative stress diminishes GSH levels 33,34 , our treatment with H 2 O 2 was expected to reduce GSH content. Pacheco et al 25 demonstrated that cadmium treatment increased ROS production, depleted intracellular GSH concentrations, and increased external GSH concentrations.…”
mentioning
confidence: 99%